Diagnostic and interventional management of infective spine diseases - Palumbo, Pierpaolo; Bruno, Federico; Arrigoni, Francesco; Zappia, Marcello; Ierardi, Anna Maria; Guglielmi, Giuseppe; Zugaro, Luigi; Carotti, Marina; Di Cesare, Ernesto; Splendiani, Alessandra; Brunese, Luca; Masciocchi, Carlo; et al. (Acta Biomedica Atenei Parmensis, 2020)
Spondylodiscitis (SD) is one of the main causes of back pain. Although the low mortality, high morbidity is related to spondilodiscitys, leading spine instability, chronic pain or neurological deficit. Diagnostic imaging plays a primary role in diagnosing spondylodiscitis. However different accuracy is highlighted by different diagnostic tool, depending also on timing of disease which represents a cardinal element for the phenotypic manifestation of the disease, beyond spatial resolution and tissue characterization proper of specific modality imaging. Conventional Radiology (CR), Computed Tomography (CT) and MRI (Magnetic Resonance Imaging) all have proven to be of primary importance in the approach to spondylodiscitis, although magnetic resonance imaging has demonstrated the greatest advantage in identifying the disease from its earliest stages, demonstrating high sensitivity and specificity (92% and 96%, respectively). This review focus on the role of different imaging modality in the approach to the spondylodiscitis, also addressing the role of interventional radiology that is pivotal not only for a diagnosis of certainty through biopsy, but also for a minimally-invasive treatment of paravertebral abscesses spondylodiscitis-related.